Information System for Distribution of Superior Livestock Assistance at BPTU-HPT Indrapuri, Aceh Besar - Nanda, Katya (Journal Dekstop Application (JDA), 2023)
The Information System for Distribution of Superior Livestock Assistance is one of the data processing activities at BPTU-HPT Indrapuri, Aceh Besar, aimed at obtaining more directed and easily accessible information on the distribution of superior livestock assistance. In this Practical Work Report (LKP), the author discusses the issues related to the distribution of superior livestock assistance and the data management mechanisms at BPTU-HPT Indrapuri, Aceh Besar, as well as designing an Information System for Distribution of Superior Livestock Assistance using Visual BASIC.NET. The purpose of this report is to understand the issues related to the distribution of superior livestock assistance and data management at BPTU-HPT Indrapuri, Aceh Besar, as well as to create a supporting application for the Information System for Distribution of Superior Livestock Assistance using Visual BASIC.NET. The data collection for this report was conducted using two methods: literature study, which involves relevant books and other scientific works, and field study through interviews and direct observations of the relevant objects related to this Practical Work Report. The Information System for Distribution of Superior Livestock Assistance is managed by one of the administrative staff members to record and input data on the distribution of superior livestock assistance. Based on the research findings, it can be concluded that the Information System for Distribution of Superior Livestock Assistance at BPTU-HPT Indrapuri, Aceh Besar, follows the established procedures and utilizes computers with Visual BASIC.NET programming language and Microsoft Access 2003 as its database